Characterization of Blimp-1 function in effector regulatory T cells. (July 2018) - Cretney, Erika; Leung, Patrick SK.; Trezise, Stephanie; Newman, Dane M.; Rankin, Lucille C.; Teh, Charis E.; Putoczki, Tracy L.; Gray, Daniel HD.; Belz, Gabrielle T.; Mielke, Lisa A.; Dias, Sheila; Nutt, Stephen L.
Abstract: Regulatory T (Treg ) cells maintain immunological tolerance in steady-state and after immune challenge. Activated Treg cells can undergo further differentiation into an effector state that highly express genes critical for Treg cell function, including ICOS, TIGIT and IL-10, although how this process is controlled is poorly understood. Effector Treg cells also specifically express the transcriptional regulator Blimp-1 whose expression overlaps with many of the canonical markers associated with effector Treg cells, although not all ICOS + TIGIT + Treg cells express Blimp-1 or IL-10. In this study, we addressed the role of Blimp-1 in effector Treg cell function. Mice lacking Blimp-1 specifically in Treg cells mature normally, but succumb to a multi-organ inflammatory disease later in life. Blimp-1 is not required for Treg cell differentiation, with mutant mice having increased numbers of effector Treg cells, but regulated a suite of genes involved in cell signaling, communication and survival, as well as being essential for the expression of the immune modulatory cytokine IL-10. Thus, Blimp-1 is a marker of effector Treg cells in all contexts examined and is required for the full functionality of these cells during aging. Highlights: Within the regulatory T cell lineage Blimp-1 expression is restricted to those cells showing an effector phenotype. Inactivation of Blimp-1 specifically in regulatory T cells results in lethal autoimmune disease. Blimp-1 regulates genes involved in signaling and function, but is not required for effector regulatory T cell identity. Blimp-1 is essential for IL-10 expression in regulatory T cells.